The Islamization of Knowledge and Some Methodological Issues in Paradigm Building: The General Case of Social Science with a Special Focus on Economics (American Journal of Islam and Society, 1987)
I. Scientific Justification for the Islamization of KnowledgeThe need for the Islamization of knowledge as a means to revive theleadership of the Islamic Umma in the world has been explained over a periodof many years by Dr. ‘AbdulHamid ’AbuSulayman. A clear conceptualizationof this Islamization, based on Tawhid, was first proposed by ProfessorIsma‘il Raji al Faruqi 1982 and presented as both a theoretical paradigm anda practical scientific research program.Both the theory and program have been attacked as unscientific, becausethey are not descriptive but rather are normative. They call for the reorganizationof knowledge into a new framework that does not grow out of the oldsecular framework of modem thought. Furthermore, Professor al Faruqi’sparadigm and praxis call for the pursuit of value-laden goals, that is, for the“ought-to-be” not only as an end in itself but as a guide and methdology for thestudy of what “is.”A thesis of this article is that the whole concept known as “Islamization ofKnowledge,” developed by Drs. ’AbuSulayman and al Faruqi, is thoroughlyscientific in the sense used by modem historians and philosophers of science.Theoreticians in the Islamization of Knowledge claim they are laying the ...